SEKTOR EKONOMI UNGGULAN DI KABUPATEN SEKADAU PERIODE 2006 2010 - B01107016, JIMI FREDIKSON (Jurnal Curvanomic, 2013)
The title of the study is "Economic Sector Featured In District Sekadau Period 2006-2010". One of the indicators to measure the success of a development area is to measure regional income generated by the indicator area with Gross Regional Domestic Product (GRDP). The purpose of this study was to analyze the leading economic sectors and analyze the competitiveness of the sectors that provide high Sekadau district in the period 2006-2010. To view the base sectors in the period 2006-2010, the District Sekadau used Location Quotient analysis methods and to see the development of the components of GDP and the sector used analytical methods Shift Share. The results of the Location Quotient is known, there are two sectors of the economy are a priority development (seed), namely Agriculture and Mining and quarrying sector. Agricultural Sector with an average LQ of 1.95 and Mining and quarrying sector has an average LQ of 1.47. This suggests that these sectors are able to produce good output value (comparative advantage) and competitive against other areas. Shift Share Calculation results obtained values ??sectoral GDP Sekadau district has undergone a change or development. Value in Regency Sekadau increased Rp 139.719 billion or grew by 26.44%, while the GDP of West Kalimantan, Rp 5.524.018 billion or grew by 22.30%. Examined the ability of sectoral competitiveness, aggregate agriculture sector and trade sector, Hotel & Restaurant has a competitive advantage compared to the same sector in West Kalimantan. The shift differential value agriculture sector amounted to Rp. 23.618 Billion trade sector, Hotel & Restaurant Rp. 20.633 billion, meaning that the two sectors have high competitiveness.